Review articles Comparison of 60Co and 192Ir sources in HDR brachytherapy - Strohmaier, Stefan; Zwierzchowski, Grzegorz (Journal of Contemporary Brachytherapy, 2011)
This paper compares the isotopes 60 Co and 192 Ir as radiation sources for high-dose-rate (HDR) afterloading brachytherapy. The smaller size of 192 Ir sources made it the preferred radionuclide for temporary brachytherapy treatments. Recently also 60 Co sources have been made available with identical geometrical dimensions. This paper compares the characteristics of both nuclides in different fields of brachytherapy based on scientific literature. In an additional part of this paper reports from medical physicists of several radiation therapy institutes are discussed. The purpose of this work is to investigate the advantages or disadvantages of both radionuclides for HDR brachytherapy due to their physical differences. The motivation is to provide useful information to support decision-making procedures in the selection of equipment for brachytherapy treatment rooms. The results of this work show that no advantages or disadvantages exist for 60 Co sources compared to 192 Ir sources with regard to clinical aspects. Nevertheless, there are potential logistical advantages of 60 Co sources due to its longer half-life (5.3 years vs. 74 days), making it an interesting alternative especially in developing countries.